1988
DOI: 10.1515/zna-1988-0406
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray and NMR Study on Cerium(III) and Magnesium(II) Perchlorate Solutions

Abstract: A n X -ra y a n d N M R S tu d y o n C e r iu m ( I I I ) a n d M a g n e s iu m ( I I) P e r c h lo r a te S o lu tio n s R. Caminiti3, G. Cerioni6, G. Crisponi3, and P. Cuccaa a Istituto di Chimica Generale, Inorganica e Analitica, Via Ospedale 72, 09100 Cagliari (Italy). b Istituto di Chimica Farmaceutica e Tossicologica, Via Ospedale 72, 09100 Cagliari (Italy).Z. Naturforsch. 43 a, 317-325 (1988); received October 15, 1987 Metal-perchlorate solutions have been investigated by the X-ray scattering techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In this contribution results obtained for chromium nitrate and cerium chloride solutions are discussed. Aqueous solutions of the salts here mentioned have been discussed by several authors [26,27,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%
“…In this contribution results obtained for chromium nitrate and cerium chloride solutions are discussed. Aqueous solutions of the salts here mentioned have been discussed by several authors [26,27,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%
“…The number of water molecules that complete the second hydration sphere of Mg 2+ has been estimated in a variety of studies to be approximately 12, ,,,, but this number is much less certain. For example, in a recent molecular dynamics simulation Martinez et al found a second shell hydration number for Mg 2+ of 13.…”
Section: Introductionmentioning
confidence: 99%
“…The ambient value is consistent with the nine-fold coordination previously confirmed by other methods. [11][12][13][14][15][16][17][18][19][20] In the literature, nine water molecules are arranged in a tricapped trigonal prism configuration around Ce 3+ (Fig. 3).…”
Section: Cerium(iii) Ion Solvationmentioning
confidence: 99%
“…In the present study, we focus on the solvation of Ce 3+ as the light rare earth ions since an aqueous CeCl3 solution is an attractive catalyst for biomass 9 and Ce 3+ exerts diverse biological effects in vivo substitution in biomolecule, mainly by their resemblance to Ca 2+ ions. 10 The solvation of Ce 3+ in an ambient condition has been widely investigated by large-angle X-ray diffraction, 11 EXAFS, 12,13 Raman spectroscopy, 14 EXAFS combined with MD simulation, 15,16 Hartee-Fock MO, 17 INDO/S-CI MO, 18 and QM/MM-MD approach. 19,20 From these studies, it has been established that Ce 3+ has nine-fold coordination in tri-capped trigonal prism with the Ce 3+ -H2O distance of 2.52~2.59 Å.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation